Matrix-dependent Strain Distributions of Au and Ag Nanoparticles in a Metal-oxide-semiconductor-based Nonvolatile Memory Device - Honghua Huang; Ying Zhang; Wenyan Wei; Ting Yu; Xingfang Luo; Cailei Yuan (Nanomaterials and Nanotechnology)
The matrix-dependent strain distributions of Au and Ag nanoparticles in a metal-oxide-semiconductor based nonvolatile memory device are investigated by finite element calculations. The simulation results clearly indicate that both Au and Ag nanoparticles incur compressive strain by high-k Al2O3 and conventional SiO2 dielectrics. The strain distribution of nanoparticles is closely related to the surrounding matrix. Nanoparticles embedded in different matrices experience different compressive stresses, which provide opportunities for tailoring the microstructure of Au and Ag nanoparticles. This opens up ways for exploring strain effects on physical properties and further tunes the charge storage properties of nanoparticles.